An evaluation of a multifaceted, local quality improvement framework for long-term conditions in UK primary care - Gabel, Frank; Listl, Stefan (Family practice, 2019)
AbstractBackground. The evidence that large pay-for-performance schemes improve the health of populations is mixed—evidence regarding locally implemented schem